Prototipe dan Monitoring Penerangan Jalan Umum (PJU) Menggunakan Tenaga Surya - Rohman, Muklis Fatqur; Pambudi, Wahyu Setyo; Wati, Trisna; Prabowo, Yuliyanto Agung (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Utilizing solar energy as an alternative energy source for Indonesia's electricity needs is very appropriate because it is located in a tropical area with hot sunlight available all year round. Considering that in rural areas in Indonesia there are still many public road accesses that are not equipped with street lighting and the problem stems from the use of conventional electrical energy as a source of street lighting. The use of photovoltaics (PV) as a tool to produce electrical energy with the advantages of being environmentally friendly, low maintenance costs and zero emissions and the energy needed is available in nature and is always renewable (renewable energy). The 1 DOF (Degree OF Freedom) solar tracker mechanic is used to find the point where the sunlight is optimal, which aims to produce maximum solar panel output during energy conversion. Based on the test results, it can be concluded that solar-powered public street lighting (PJU-TS) using a mechanical solar tracker delay of 2 seconds produces a daily energy conversion of 235.20 Wh, which is more optimal than solar-powered public street lighting (PJU-TS) with solar tracker delay. 2.5 seconds amounting to 218.75 Wh and solar powered public street lighting (PJU-TS) without a solar tracker amounting to 171.34 Wh.